2008
DOI: 10.1534/genetics.108.090100
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Adsorption Rate and Optimal Lysis Time

Abstract: The first step of bacteriophage (phage) infection is the attachment of the phage virion onto a susceptible host cell. This adsorption process is usually described by mass-action kinetics, which implicitly assume an equal influence of host density and adsorption rate on the adsorption process. Therefore, an environment with high host density can be considered as equivalent to a phage endowed with a high adsorption rate, and vice versa. On the basis of this assumption, the effect of adsorption rate on the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
188
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(205 citation statements)
references
References 28 publications
9
188
2
Order By: Relevance
“…Optimal lysis time is positively correlated with adsorption rate, and phage strains with higher adsorption rates show faster lysis than those with lower adsorption rates (21). To determine if the adsorption rate provides any contribution to the delay in lysis time observed with the T-lacking mutant, we measured adsorption rates of the wild-type and mutant phages in infection of exponentially growing BL21 at 37°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Optimal lysis time is positively correlated with adsorption rate, and phage strains with higher adsorption rates show faster lysis than those with lower adsorption rates (21). To determine if the adsorption rate provides any contribution to the delay in lysis time observed with the T-lacking mutant, we measured adsorption rates of the wild-type and mutant phages in infection of exponentially growing BL21 at 37°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data reveal precision in the timing of lysis-individual cells infected by a single virus lyse on average at 65 min, with an SD of 3.5 min, implying a coefficient of variation of ≈ 5% (SI Appendix, section S9). Such precision is expected given the existence of an optimal lysis time (46)(47)(48)(49). Intuitively, if λ lysis is early then there are no viral progeny.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported that no hindrance is seen when host concentration is low because of the low fraction of volume they occupy. However, at high host concentrations, the balance shifts and the host density acts as a barrier to diffusion, hindering the process of viral spread in the surrounding medium (32,35,36). Also, as mentioned, antibiotics actually lengthened the productive/plaque enlargement phase (during which the bulk of plaque enlargement occurs), as bacterial lawns take longer to mature under these conditions, thus delaying the onset of lawn maturation and giving more time to progeny virions to add onto the growing plaque during this period.…”
Section: Discussionmentioning
confidence: 99%